2013
DOI: 10.1259/bjr.20130015
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of modelled tumour control probability based on individual measurements ofin vitroradiosensitivity and potential doubling time

Abstract: Objective: The aim of this study was to compare patient-specific radiobiological parameters with population averages in predicting the clinical outcome after radiotherapy (RT) using a tumour control probability (TCP) model based on the biological effective dose (BED).Methods: A previously published study of 46 head and neck carcinomas with individually identified radiobiological parameters, radiosensitivity and potential doubling time (T pot ), and known tumour size was investigated. These patients had all bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…To calculate surviving fraction (SF) and tumor control probability (TCP) with regard to biologically effective dose (BED), by using breast cancer radiobiological parameters and the following equations: [14][15][16] ln(SF)= -E [17,18] I S S N 2347-3 4 8 7 Where: n (the number of well-spaced and identical fractions) =15 fractions, d (the dose per fraction) =2.67 Gy (hypofractionation regimen 40 Gy/15 fractions) [16]. (α/β) ratio (is the linear to quadratic coefficients in the linear quadratic (LQ) model, and represents the dose at which single and double-hit killing events are equal in number; at higher doses double-hit killing events start to progressively dominate) = 4 Gy [19].…”
Section: Radiobiological Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…To calculate surviving fraction (SF) and tumor control probability (TCP) with regard to biologically effective dose (BED), by using breast cancer radiobiological parameters and the following equations: [14][15][16] ln(SF)= -E [17,18] I S S N 2347-3 4 8 7 Where: n (the number of well-spaced and identical fractions) =15 fractions, d (the dose per fraction) =2.67 Gy (hypofractionation regimen 40 Gy/15 fractions) [16]. (α/β) ratio (is the linear to quadratic coefficients in the linear quadratic (LQ) model, and represents the dose at which single and double-hit killing events are equal in number; at higher doses double-hit killing events start to progressively dominate) = 4 Gy [19].…”
Section: Radiobiological Calculationsmentioning
confidence: 99%
“…N0 (the initial number of clonogens in the tumor) = 109. V [15]. The density of clonogens per cubic centimeter (cc) =109 [15].…”
Section: Radiobiological Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large multicentre analysis also failed to correlate experimental determinations of T pot with treatment outcome in head and neck cancers [34]. However, a more recent analysis has shown that pretreatment proliferation parameters are better predictors of outcome when other factors like tumour size, individual radiosensitivity and overall treatment time are taken into account [35].…”
Section: Repopulationmentioning
confidence: 99%
“…Radiotherapy has been commonly used in clinics for treatment of cancer 2 . The total dose estimation for patient plays an important role in maximizing the effectiveness of treatment which is decided by various factors like type of tumour, size, and proliferation 3 .…”
Section: Introductionmentioning
confidence: 99%